KESULITAN DAN SOLUSI DALAM MENULIS SKRIPSI BAHASA INGGRIS (Sebuah Investigasi Berdasarkan Perspektif Mahasiswa dan Dosen di Program Studi Pendidikan Bahasa Inggris, Universitas Pekalongan) - Sarlita Dewi Mtra; Dwi Ario Fajar (LPPM Universitas Pekalongan, 2015)
This research aims to analyze the English Education students’ of Universitas Pekalongan problems in writing final project in English. The causes are viewed from students’ and the lecturers perspective as the advisor and also what are supposed to do to help the student minimize the problems in writing final project. This study used descriptive qualitative method that fully describe the problems as well as solutions in writing final projects. The deep analysis has been done from the student’s and the lecturer’s perspectives. After conducting a survey by doing some interviews and distributing questionnaires, we found that there are so many factors that affects the studnts’ difficulties in finishing their final projects.